Private and Public Relative Performance Information under Different Compensation Contracts - Tafkov, Ivo D. (The Accounting Review, 2013)
ABSTRACT: This study investigates the conditions under which providing relative performance information to employees has a positive effect on performance when compensation is not tied to peer performance. Specifically, I investigate, via an experiment, the effect of relative performance information (present or absent) on performance under two compensation contracts (flat-wage or individual performance-based). Given the presence of relative performance information, I examine the effect of the type of relative performance information (private or public) on performance. Using theory from psychology, I predict and find that relative performance information positively affects performance under the two compensation contracts and that this positive effect is greater under an individual performance-based contract than under a flat-wage contract. I also predict and find that, although both public and private relative performance information have a positive effect on performance, the effect is greater when relative performance information is public. Data Availability: Data are available from the author on request.